Determinants of financial vulnerability among credit counselling and debt management agency customers - Chong, Kok Fei (2021)
During the turbulent time where financial and economic are being unstable, a growing number of households are facing difficulties in making ends meet and not resilient to cope with unexpected expenses. These households are deemed to be financially vulnerable, and the financial vulnerability of households can exert undesired impacts on economic growth and societal problems. In order to curb the financial vulnerability issue, the primary objective of this study is to investigate the factors influencing financial vulnerability among Malaysian households. Two theories, namely family resource management model and self-efficacy theory were employed to serve as the basis of the research fieldwork. Four factors were proposed as relevant elements in the process of reducing financial vulnerability. This study proposes the input (i.e., self-efficacy, financial literacy, gender, and age), throughput (i.e., financial behavior) and output (financial vulnerability) mechanism. In addition, this study further examines the moderating effect of self-efficacy in the relationship between financial literacy and financial behavior. In terms of data collection, a multi-stage random sampling technique was used to sample a total of 640 usable responses from AKPK centers in Malaysia. After discarding unusable responses, the collected data was analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The study followed standard of PLS-SEM guideline by examining measurement model before proceeding to structural model. The results indicated all the measurements were satisfactory in terms of reliability and validity. The model explained sufficient variance of financial vulnerability (R²= 0.292). Results indicated that gender (β= -0.07, p≤ 0.05) and self-efficacy (β= 0.44, p≤ 0.05) significantly influences financial behavior. Financial behavior negatively influences financial vulnerability (β= -0.54, p≤ 0.05). The mediating effect of financial behavior in the relationship between self-efficacy and financial vulnerability was identified (β= -0.24, p≤ 0.05). The finding supports the moderating effect of self-efficacy in the relationship between financial literacy and financial behavior (β= 0.12, p≤ 0.05), indicating that the relationship between financial literacy and financial behavior is stronger when self-efficacy of Malaysian households is high. Other than that, the relationship between financial literacy and financial vulnerability was not significant (p≥0.05). The findings obtained from the analysis were in good agreement with relevant theories, and adds to the findings of previous studies. Besides offering some important implications to the scholarly works, this study also provides a predictive model that presents insightful implications for households and policy makers, particularly regarding the important yet overlooked role of self-efficacy and overrated role of financial literacy. Lastly, limitations of the study and recommendations for further research were outlined.